Neonatal and short-term outcome after late vertical transmission in congenital CMV-infected fetuses following primary first-trimester maternal seroconversion - Gunnar Naulaers; Bart De Keersmaecker; Luc De Catte; Katrien Lagrou; Sanne Vanwinkel; Katrien Jansen (BMJ Publishing Group, 2024)
Objective To document the course of neonatal and short-term outcomes in pregnancies after first trimester CMV (cytomegalovirus) seroconversion and negative amniotic fluid (AF) CMV PCR.Methods We included 375 patients with a first-trimester CMV seroconversion and amniocentesis at ≥21 weeks. Termination of pregnancy (TOP) was offered in case antenatally severe CMV-related fetopathy was documented either by ultrasound or by MRI. AF CMV PCR-negative fetuses underwent a PCR CMV on neonatal urine (NU). Perinatal and short-term infant outcomes were investigated by a questionnaire, sent to parents.Results AF CMV PCR was positive in 118/375 cases (31.4%). TOP was performed in 46/118 (38.9%) and fetal demise occurred twice. Questionnaires were sent to 327 patients with an overall response rate of 77%. Three groups were considered: Group 1: the early infected group (AF CMV PCR positive; N=62), group 2: the late infected group (AF CMV PCR negative, NU CMV PCR positive; N=7) and group 3: the control group (AF+NU CMV PCR negative; N=160). Compared with group 3, group 1 was more frequently symptomatic at birth (6.2% vs 19.4%; p=0.006). In short-term follow-up, hearing impairment (23.5%; p<0.001), mild motor deficit - defined as abnormal early motor development or the need for physiotherapy in later life (21.6%; p=0.005) - and subnormal vision (15.7%; p=0.02) were significantly more frequent. Compared with group 3, group 2 showed more often jaundice (57.1%; p=0.04) and petechiae (28.6%; p=0.04) at birth, but other short-term symptoms were lacking.Conclusion Although neonates may screen positive on urine for CMV after an AF CMV negative PCR, they show rarely and only mild sequelae in early life.